Pengaruh Islamic Leadership Dan Budaya Religiusitas Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Karyawan Sebagai Variabel Intervening Pada PT. Bank Syariah Indonesia Kantor Area Malang - Iga Ade Mirela; Rois Arifin; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This examine goals to decide and examine the impact of Islamic management and religious subculture on employee performance thru task pleasure as an intervening at PT. bank Syariah Indonesia Malang vicinity workplace. This studies is informal associative research the usage of a quantitative approach. The pattern of this observe used a saturated pattern, particularly eployees of PT. bank Syariah Indonesia location workplace as many as 80 personnel. gathering facts using a valid and dependable questionnaire. statistics analysis became accomplished the usage of more than one regression linier analysis. The end result of the take a look at found that : 1) Islamic leadership has enormous poor effect on employee overall performance. 2) lifestyle religiosity has a sizeable negative on worker overall performance. three) Islamic leadership has a great bad impact on process pride. 4) Cultural religiosity has no considerable positive effect on job satisfaction. 6) Islamic management has a significant negative impact on worker performace via task pleasure as an intervening variable. 7) religious culture has a significant poor impact on worker overall performance thru activity satisfactionas an intervening variable. Keywords: Islamic Leadership, Religious Subculture, Worker Performance, And Job Delight.